A Margarine-Supplemented Diet Alone and in Combination with Chamomile Decoction Decreases Food Intake but Has a Mild Effect on Body Mass in Mice - Hurza, Viktoriia; Vatashchuk, Myroslava; Bayliak, Maria (Journal of Vasyl Stefanyk Precarpathian National University. Biology, 2023)
The Western diet is one of the most popular eating styles in recent years. It is based on foods high in fat, sugar and salt. It is known that excessive consumption of this type of food causes the development of metabolic syndrome (MetS), characterized by obesity, insulin resistance, high cholesterol and blood glucose levels, and high blood pressure. The aim of this study was to test whether diet enriched with margarine, as the main component of Western diet foods, to be able to induce obesity in experimental mice and whether chamomile water decoction (CWD) was able to mitigate effects of margarine-containing diet. The latter, as can be seen from previous studies, has a high potential to mitigate MetS. We also decided to test whether a diet with margarine and CWD would have the same effect on young mice of both sexes. For the experiment, one-month-old male and female mice of the C57Bl/6J line were used. The mice were divided into three groups, six in each. The first group (control) consumed basic food and water during the entire experiment. The second group consumed basic food and 70% fat margarine, added in excess in a separate dish, and drank water. The third group consumed basic food and margarine (70% fat) and drank CWD diluted in drinking water. The experiment lasted four months. During the experiment, the animals' body mass, food and water consumption were monitored with calculation of body mass index (BMI) and Lee obesity index at the end of feeding period. The results showed that the addition of margarine to the basic diet caused an increase in body mass in females, but not in males, but did not changed BMI or in the Lee obesity index in both sexes. The addition of CWD to the margarine-containing diet caused a downward trend in body mass gain and reduced the Lee obesity index in both sexes. Mice, which were fed margarine-containing diet, showed by 15% and 30% by lower total food intake in males and females, respectively, as compared with the control group. At the same time, no difference in a number of calories was observed between control and margarine-fed groups. On the margarine-supplemented diet, males consumed an average of 70% basal food and 30% margarine, while females' diet consisted of approximately 50% basal food and 50% margarine In addition, water consumption decreased in mice fed margarine alone and in the CWD background.. Consumption of CWD with a margarine diet increased food intake in males to the level of the control group, but had no similar effect in females. As in margarine-fed mice, mice fed margarine and CWD showed a downward trend in water consumption. It can be concluded that the mice were not obese.